A novel (????, ????) multi-secret image sharing scheme harnessing RNA cryptography and 1-D group cellular automata - Abdul, Yasmin; Ramasamy, Venkatesan; Kukaram, Gaverchand (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
In the modern landscape, securing digital media is crucial, as digital images are increasingly disseminated through unsecured channels. Therefore, image encryption is widely employed, transforming visual data into an unreadable format to enhance image security and prevent unauthorized access. This paper proposes an efficient (????, ????) multi-secret image sharing (MSIS) scheme that leverages ribonucleic acid (RNA) cryptography and one-dimensional (1-D) group cellular automata (GCA) rules. The (????, ????) MSIS scheme encrypts ???? images into ???? distinct shares, necessitating all ???? shares for decryption to accurately reconstruct the original ???? images. Initially, a key image is generated using RNA cryptography, harnessing the extensive sequence variability and inherent complexity of RNA. This secret key is then used to encrypt ???? images in the primary phase. In the secondary phase, pixel values are transformed through multiple processes, with randomness achieved by executing a key function derived from GCA, known for its reversible properties, computational efficiency, and robustness against cryptographic attacks. The proposed model, implemented in Python, is validated through experimental results, demonstrating its effectiveness in resisting a broad spectrum of attacks, including statistical, entropy, differential, and pixel parity analyses. These findings affirm the model's durability, security, and resilience, underscoring its superior performance compared to existing models.